Clinical characteristics of temporomandibular disorders presenting posterior open bite - A report of 12 cases - Min-Goo Kang; Yu-Jin Park; Kyung-Hoe Huh; Hong-Seop Kho (Elsevier, 2021)
Background/purpose: There is a paucity of comprehensive information about posterior open bite (POB) in patients with temporomandibular disorders (TMD) because of its rare prevalence. The purpose of this study was to investigate the etiologies, clinical characteristics, and treatment outcomes of patients with TMD presenting POB. Materials and methods: This study includes a careful review of medical records and imaging findings of 12 patients with TMD (seven men and five women, 50.9 ± 19.2 years, 15-72 years) complaining of POB. Results: In total, 11 had unilateral POB, whereas 1 had bilateral POB. In 11 patients, POB was caused by inflammatory disorders of temporomandibular joint (TMJ). In the remaining one patient, TMJ medial disc displacement (MDD) was responsible for POB. Of 11 patients with inflammatory conditions of TMJ, four patients had unilateral TMJ internal derangement (ID), two had bilateral TMJ ID, and one had rheumatism. POB was resolved in 10 of 11 patients with TMJ inflammation following the administration of non-steroidal anti-inflammatory drugs and self-management instructions. Prosthodontic treatment was needed in one patient to resolve POB. POB was resolved in the patient with TMJ MDD after stabilization splint therapy. Conclusion: POB in patients with TMD was mostly caused by inflammatory disorders of TMJ. TMJ MDD could also be a reason. Although almost all POB was resolved by conservative treatments including medications, the possibility of prosthodontic, orthodontic, or surgical treatments also must be considered.